Prevalence of Paternal Prenatal Depression and Its Associated Factors in Saudi Arabia [Response to Letter] - Younis AS; Julaidan GS; Alsuwaylimi RA; Almajed BM; AlShammari RT; AlFirm RB; Alfarra LA (Dove Medical Press, 2024)
Afnan S Younis,1 Gharam S Julaidan,2 Renad A Alsuwaylimi,2 Buthaina M Almajed,2 Rahaf T AlShammari,2 Renad B AlFirm,2 Lena A Alfarra3 1Department of Family and Community Medicine, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 2College of Medicine, King Saud University, Riyadh, Saudi Arabia; 3Department of Obstetrics and Gynecology, King Saud University Medical City, Riyadh, Saudi ArabiaCorrespondence: Afnan S Younis, Email afnan.younis@gmail.com